If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2x + 10 = 0 Reorder the terms: 10 + 3x + 2x = 0 Combine like terms: 3x + 2x = 5x 10 + 5x = 0 Solving 10 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 5x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 5x = 0 + -10 5x = 0 + -10 Combine like terms: 0 + -10 = -10 5x = -10 Divide each side by '5'. x = -2 Simplifying x = -2
| -15x-40=2 | | 3n-14=76 | | 8+-3x=23 | | 14-3n=76 | | .7(.1x+.7)=-.07 | | -8-18x-10=-4 | | V=4wxy | | n^3-6n^2-n=-6 | | 2t^2-7=13t | | 7x+5-1.3=46-.3x | | .6x^2-8x-20=0 | | x^4+2x^2+5=0 | | e^9y=11 | | x^2-6x+36=x | | f-3.3=5.7 | | 5v^2-32=36v | | 2e-12=7c+8 | | 48x+64-55x^2=0 | | n/3=2.4 | | 35x+5+5x=-2 | | -16t^2+30t+5=6 | | y^2-4y+16=2y | | 28x^2+132x-40=0 | | 18+3x=2x-12 | | (y-4)(y+4)=2y | | x^2-5x=75 | | 10x^2+2x+1=501 | | 7+32x+12=3 | | 5n+20=70 | | 39=t+4t | | (X-3)(x+4)=-4(4+x) | | 17x+56=23x+38 |